2021
DOI: 10.1038/s41586-021-04387-1
|View full text |Cite
|
Sign up to set email alerts
|

Omicron extensively but incompletely escapes Pfizer BNT162b2 neutralization

Abstract: This is a PDF file of a peer-reviewed paper that has been accepted for publication. Although unedited, the content has been subjected to preliminary formatting. Nature is providing this early version of the typeset paper as a service to our authors and readers. The text and figures will undergo copyediting and a proof review before the paper is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers apply.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

85
843
5
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 1,058 publications
(976 citation statements)
references
References 33 publications
85
843
5
3
Order By: Relevance
“…In-vitro data suggest lower titres of neutralising antibodies against omicron compared to other SARS-CoV-2 lineages following BNT162b2 vaccination but increased titres after a third dose, 10 , 11 , 12 supporting calls for booster doses while the omicron variant appears to be spreading globally. Our study, however, demonstrates insufficient prevention of symptomatic infection in otherwise healthy individuals who had received three doses of COVID-19 mRNA vaccines.…”
mentioning
confidence: 99%
“…In-vitro data suggest lower titres of neutralising antibodies against omicron compared to other SARS-CoV-2 lineages following BNT162b2 vaccination but increased titres after a third dose, 10 , 11 , 12 supporting calls for booster doses while the omicron variant appears to be spreading globally. Our study, however, demonstrates insufficient prevention of symptomatic infection in otherwise healthy individuals who had received three doses of COVID-19 mRNA vaccines.…”
mentioning
confidence: 99%
“…The potential antigenic impact of adaptive S1 mutations, which are accruing at pace over 4 times that of influenza H3N2 (Figure 2, Figure S5), suggests that it may become necessary to update the SARS-CoV-2 vaccine strain. Indeed, the emergence of the Omicron Variant of Concern demonstrated a SARS-CoV-2 virus with an extraordinarily high number of S1 substitutions [26] that spread rapidly across the world and showed significantly reduced neutralization titers relative to preceding variants [27]. With Omicron, we now know that significant antigenic variants can emerge with highly modified S1 domains.…”
Section: Discussionmentioning
confidence: 99%
“…The Omicron variant of SARS-CoV-2 escapes immunity generated by vaccines and previous infections 1 , 2 yet seems to have some unexpected advantages over the other variants we have experienced so far. Firstly, and most importantly, strong evidence is emerging that the disease induced by infection with Omicron is considerably milder at the population level (Fig.…”
mentioning
confidence: 83%
“…Studies looking at neutralizing immunity against Omicron showed that although Omicron can escape this immunity, it is essentially a numbers game. Increased levels of neutralizing antibodies owing to booster vaccines or a combination of previous infection and vaccination counteract viral escape, so that antibody neutralization against Omicron in these groups is more or less equivalent to the neutralization seen against variants such as Delta in those who are fully vaccinated but not boosted 1 , 2 . Furthermore, the levels of antibody-mediated immunity required for protection against severe disease are much lower and may be achieved by vaccination alone, even in the absence of boosters 8 .…”
mentioning
confidence: 99%